Odtwarzanie palimpsestu uniwersytetu w jego codzienności = Reconstructing the palimpsest of the university in its everyday life - Nojszewski, Olgierd (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to define the identity of the university and confront it with the everyday practices of this institution and the academic community. The foundations for the university`s mission - understood as the pursuit of truth - are autonomy and collegiality.
Keywords: akademickość; uniwersytet; autonomia uniwersytetów; academic ethos; university; university autonomy